Solution Structures of PPARγ2/RXRα Complexes. (18th December 2012) - Osz, Judit; Pethoukhov, Maxim V.; Sirigu, Serena; Svergun, Dmitri I.; Moras, Dino; Rochel, Natacha
Abstract : PPAR γ is a key regulator of glucose homeostasis and insulin sensitization. PPAR γ must heterodimerize with its dimeric partner, the retinoid X receptor (RXR), to bind DNA and associated coactivators such as p160 family members or PGC-1 α to regulate gene networks. To understand how coactivators are recognized by the functional heterodimer PPAR γ /RXR α and to determine the topological organization of the complexes, we performed a structural study using small angle X-ray scattering of PPAR γ /RXR α in complex with DNA from regulated gene and the TIF2 receptor interacting domain (RID). The solution structures reveal an asymmetry of the overall structure due to the crucial role of the DNA in positioning the heterodimer and indicate asymmetrical binding of TIF2 to the heterodimer.